Technology-Organization-Environment Model and Technology Acceptance Model in Adoption of Social Media Marketing on SMEs Tourism - SUGANDINI, Dyah; EFFENDI, Mohamad Irhas; ISTANTO, Yuni; ARUNDATI, Rahajeng; RAHMAWATI, Esti Dwi (Journal of Environmental Management and Tourism, 2019)
This study aims to analyze the model of social media adoption in SMEs tourism in Special Region of Yogyakarta, with antecedents’ managers innovativeness, pressure from competitors, barrier to adoption, Perceived Usefulness (PU), Perceived Ease of Use (PEU) and attitude. Two theoretical approaches are used, namely Technology Acceptance Model and Technology-organization-environment (TOE) models. This research is a survey research. Respondents in this study are managers of SMEs tourism. The social media adoption model was tested empirically using 200 respondents. Structural Equation Model is used to analyze research data. This study analyzes the social media adoption of tourism SMEs in developing countries, because although there are many studies on social media adoption in developing countries, very few focus on social media adoption in the small-scale tourism industry. This research integrates TAM and TOE in exploring the adoption of social media marketing on SMEs tourism by adding a barrier to adoption. The results of this study indicate that the TAM model combined with TOE supports the social media adoption model. Most of the variables studied were largely significant, but this study could not justify the influence of barriers on social media adoption.